1990
DOI: 10.1182/blood.v76.11.2397.2397
|View full text |Cite
|
Sign up to set email alerts
|

A new method for isolation of reticulocytes: positive selection of human reticulocytes by immunomagnetic separation

Abstract: A method for isolating pure reticulocytes from leukocyte-depleted blood of normal persons is presented. The separation was achieved using an immunomagnetic technique. A monoclonal mouse antibody against human transferrin receptor was bound to magnetic beads conjugated with sheep antimouse antibody. The recovery of reticulocytes from peripheral blood was 15% to 42%. Blood used for isolation of reticulocytes could be stored for 4 days at 22 degrees C without altering the yield of reticulocytes. At 37 degrees C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Simple differential centrifugation (DC) provides a method to enrich reticulocytes from peripheral blood, but the enrichment is low (<3%) ; when used on hemochromatosis blood, DC can attain enrichments of 15% reticulocytes . Affinity‐based separation techniques and the direct growth of reticulocytes allows high purity (>90%) that is not matched by enrichments using AMPSs, but these methods are expensive and impractical for routine use . DC‐Percoll provides a means to enrich reticulocytes, but this method requires two separate centrifugation steps and two extraction steps; variation between steps compound to reduce reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple differential centrifugation (DC) provides a method to enrich reticulocytes from peripheral blood, but the enrichment is low (<3%) ; when used on hemochromatosis blood, DC can attain enrichments of 15% reticulocytes . Affinity‐based separation techniques and the direct growth of reticulocytes allows high purity (>90%) that is not matched by enrichments using AMPSs, but these methods are expensive and impractical for routine use . DC‐Percoll provides a means to enrich reticulocytes, but this method requires two separate centrifugation steps and two extraction steps; variation between steps compound to reduce reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods to obtain substantially enriched (>10% of erythrocytes) samples of reticulocytes are impractical, expensive, labor‐intensive, or not satisfactory for routine use for applications that require reproducible yields and readily available sources of blood. These methods include culture and development of progenitors , affinity‐based separation , differential centrifugation , and centrifugation over layered gradients . We describe these methods in detail in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the M 2 isozyme in PK‐deficient erythrocytes makes it difficult to diagnose PK deficiency in dogs using assays that measure total erythrocyte PK activity. Reticulocytes have considerably higher PK activity than do mature erythrocytes 34,35. Consequently, the finding of PK activity within or slightly above the reference interval in a dog with marked reticulocytosis is highly suggestive of PK deficiency.…”
Section: Pyruvate Kinase Deficiencymentioning
confidence: 99%
“…It has been shown that transferrin receptors disappear during maturation, thereby suggesting that they are specific for immature red cells (Frazier et al, 1982). Bearing such difference in mind, a purification protocol using anti‐transferrin antibodies coupled to magnetic beads was developed (Brun et al, 1990); the results revealed 15–42% reticulocyte enrichment. However, the difficulty of eluting cells coupled to beads has been the main factor limiting this method.…”
Section: Reticulocyte Sourcesmentioning
confidence: 99%